Qur’anic Ecotheology and the Ethics of Forest Protection in Indonesia - Afrizal Nur; Hayati bin Husin; Alwizar; Muhammad Yasir (UIN Sunan Kalijaga Yogyakarta, 2025)
Indonesia’s alarming rate of forest degradation, amounting to approximately 1.45 million hectares lost in the past five years, has far-reaching ecological, climatic, and socio-cultural consequences. Beyond the environmental dimension, this crisis raises profound theological concerns, especially within the Islamic worldview, which frames human beings as khalifah (stewards) entrusted with preserving the Earth. The Qur’an emphasizes the importance of ecological balance (mīzān) and explicitly condemns destruction (fasād) on Earth, suggesting that environmental care is a moral and spiritual obligation. This study explores the relevance of Islamic Eco theological principles to Indonesia’s Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction. Using a hermeneutic analysis of selected Qur’anic verses (Al-Baqarah [2]:164, Al-Aʿrāf [7]:56, and Al-Aḥzāb [33]:72), combined with comparative legal analysis, the research highlights the alignment between religious ethics and statutory forest protection. While the law reflects procedural strength, it lacks integration with deeper Eco theological values that could inspire stronger public commitment. It is understandable that legal frameworks often rely on institutional enforcement, yet in religious societies such as Indonesia, faith-based approaches can enhance policy legitimacy and moral motivation. This study argues for the integration of Qur’anic values, such as stewardship, moderation, and accountability, into environmental education and legal application. Doing so may transform forest conservation from a mere regulatory task into an act of spiritual devotion and collective responsibility. Further empirical research is needed to examine how such integration plays out in practice within local communities, offering valuable insights for more holistic and culturally grounded environmental governance.